Mother–infant interactions with infants with congenital visual impairment and associations with longitudinal outcomes in cognition and language. (18th August 2020) - Sakkalou, Elena; O'Reilly, Michelle A.; Sakki, Hanna; Springall, Clare; de Haan, Michelle; Salt, Alison T.; Dale, Naomi J.
Abstract : Background: This study investigated mother–infant interactions, including maternal maintaining of infant attentional focus and sensitivity, with infants with congenital severe and profound visual impairment (VI) and the association with developmental trajectories from one to three years. Method: Fifty‐five infants and mothers were video‐recorded playing together with a standard set of toys at Time 1 (T1) mean age 12.95 months (8.13–17.05 months). Maintain was categorized as the mother following and maintaining the child's focus, and Sensitivity, the mother's responsiveness and contingency to infant behaviour. Vision level was measured using the Near Detection Scale. Cognition and language were measured at T1, 12 months later (T2) and 24 months later (T3) using the Reynell‐Zinkin Scales. Results: Cross‐sectional analyses showed that mothers of infants with severe VI (basic form vision) produced higher rates of Maintain compared to those with children with profound VI (light perception at best). Linear mixed‐effects models examining developmental progression from T1 to T3 (controlling for vision level) showed an average increase of 5 DQ points (CI 95%: 1.03–9.08) in verbal comprehension for higher Sensitivity. No significant findings were found for Maintain. Conclusions: The findings suggest that mother–infant interactions (maternal Maintain) are associated with level of vision at infancy, but only maternal Sensitivity has a long‐term positive association with advances in verbal comprehension from infancy to about three years. They highlight the need for incorporating strategies related to parent–infant interactions, including increased sensitivity, into early intervention for children with visual impairment.